2005
DOI: 10.1097/00008469-200506000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Intake of wine, beer and spirits and risk of gastric cancer

Abstract: The objective was to study prospectively the relation between quantity and type of alcohol and risk of gastric cancer. In a pooled database from three population studies conducted in 1964-1992, a total of 15,236 men and 13,227 women were followed for a total of 389,051 person-years. During follow-up 122 incident cases of gastric cancer were identified. Total alcohol intake itself was not associated with gastric cancer, but type of alcohol seemed to influence risk. Compared with non-wine drinkers, participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 21 publications
1
39
0
4
Order By: Relevance
“…From prospective population-based studies, there is a clear J-shaped relationship between the consumption of alcoholic beverages such as wine, and the risk of cardiovascular diseases including myocardial infarction, which has been extended to a reduced risk of certain cancers, type 2 diabetes and ischaemic stroke [24][25][26][27][28][29][30][31][32][33][34]. Over the last decade, evidence has accumulated which suggests that this J-shaped relationship could also be extended to the risk of cognitive dysfunction and dementias such as Alzheimer's disease and vascular dementia [35][36][37][38][39][40][41].…”
Section: J-shaped Relationship Of Alcoholic Beverages With Cognitive mentioning
confidence: 99%
“…From prospective population-based studies, there is a clear J-shaped relationship between the consumption of alcoholic beverages such as wine, and the risk of cardiovascular diseases including myocardial infarction, which has been extended to a reduced risk of certain cancers, type 2 diabetes and ischaemic stroke [24][25][26][27][28][29][30][31][32][33][34]. Over the last decade, evidence has accumulated which suggests that this J-shaped relationship could also be extended to the risk of cognitive dysfunction and dementias such as Alzheimer's disease and vascular dementia [35][36][37][38][39][40][41].…”
Section: J-shaped Relationship Of Alcoholic Beverages With Cognitive mentioning
confidence: 99%
“…In addition, Danish researchers have found that moderate wine consumption is associated with lower frequency of cancer in the upper digestive tract [42]; gastric cancer [43]; hip fracture [44]; and lung cancer [45].…”
Section: Introductionmentioning
confidence: 99%
“…1 Case-control 2-12 and cohort studies 13-15 on alcohol and gastric cancer published since that review have found either no significant association 3,[5][6][7][11][12][13][14][15] or a statistically significant increased risk of overall [8][9][10] or noncardia gastric cancer 2,4 associated with high alcohol consumption. Despite a large number of epidemiological studies concerning the relation between alcohol consumption and risk of gastric cancer, most have been case-control investigations, which are more susceptible to systematic bias than prospective cohort studies.…”
mentioning
confidence: 99%